ANALYSIS OF 3D MODELLING OF BASEMENT MAGNETIC USING MAGB_INV IN CENDRAWASIH BAY, PAPUA - Abigail Paraskah Kawab, Gracia
Magnetic basement has a relationship with information on potential areas that produce hydrocarbons. The sediment thickness information is associated with the depth of the magnetic basement. Determination of the geometry of the 3D magnetic is one of the main objectives of magnetic interpretation of an area. The MagB_Inv program is a MATLAB program that is useful for obtaining 3D models of magnetic basement. This program is able to process large amounts of data and perform fast and accurate calculations. The calculation used in this program is the inverse Fourier transform and uses a high cut-filter to avoid high-frequency instability. In this study, the MagB_Inv program was applied to the Cendrawasih Bay area, Papua; areas of sedimentary basins that have been drilled and have hydrocarbon prospects. The results obtained show that the thickness of the sediment in the study area is around 7-25 km. The maximum sediment thickness in the Biak Yapen Basin is about 20 km and in the Cendrawasih Basin about 25 km